An evaluation of the effectiveness of the skills development programme in shelters accommodating survivors of domestic violence in Gauteng Province, Tshwane Region - Moganedi, Matshemo Joyce (My University, 2021)
In South Africa, shelters that accommodate survivors of domestic violence also adopted the Skills Development Programme with the intention of empowering survivors to be financially self-reliant. In shelters the Skills Development Programme is rendered for a period of six months depending on the stay of the survivors. Despite the provision of the Programme, which has been identified as intervention strategies towards poverty alleviation, it is evident that the level of skills training provided does not conform to the identified skills shortage in the economy. Sometimes it is due to limited time which the training had provided.The programme is not sustainable, and as a result, there is a high beneficiary turnover. Furthermore, resources of training beneficiaries to be independent are limited. Monitoring and evaluation is also poor. This programme is acknowledged to be expensive. The graduation from this programme does not mean success for the survivors. Instead, it results in the participants going back to poverty status and be dependent on government resources to make a living post-institutionalisation. This study titled “An evaluation of the effectiveness of Skills Development Programmes in the shelters accommodating survivors of domestic violence in Gauteng Province, Tshwane Region” evaluated the effectiveness of the said programme. It has adopted a qualitative approach which was evaluative in nature, guided by the Stages of Change Model (Trans-theoretical Model) underpinned by Theory of Reasoned Action. The participants consisted of three (3) different sets. They were survivors (individuals) of domestic violence from the shelters, shelter managers and a focus group made out of those individual survivors. Five (5) survivors of domestic violence and five (5) shelter managers were interviewed on a face to face basis. Semi-structured interviews were employed to collect data. This was followed by a focus group discussion. Multiple sources provided verification and trustworthiness while complementing similar data. As a result, more comprehensive data was obtained. During the data analysis process, different themes emerged. These were presented in the form of a report. It was evident that the Skills Development Programme presented in the shelters is not effective to help survivors of domestic violence to be financially self-reliant. However, there is a potential in the programme if it can be well resourced.
Thesis (Ph. D. (Social Work)) -- University of Limpopo, 2021
Keywords: Skills Development Programme; Shelters; Domestic violence; Tshwane Region; Training centre; Occupational training; Vocational education; Training